Cost and time risk factors in construction projects in the Dominican Republic - Fernández-Valderrama, Pedro; Ureña-Estrella, Crismal; Moyano, Juan; Bienvenido-Huertas, David (Frontiers in Built Environment, 2024)
The building sector is very dynamic and complex, so construction works are surrounded by uncertainties. The deficiencies of this sector are mainly related to poor project planning and management, resulting in losses because of missed deadlines, cost overruns, reworks, and unsatisfied clients. For a project to be successful, all the parties involved should work together to effectively manage the risks that could emerge in the project life cycle. This research defines and establishes a classification of the factors causing cost and time deviations in construction projects in the Dominican Republic. For this purpose, the most common factors are compiled, and their risk levels are determined by using the data obtained in a survey in which professionals from the building sector participated. The indexes marked by the participants show that the serious risk factors are design variations and the variations made by clients, a tight project schedule and the preparation of bid offers, deficiencies in the work planning and schedule, the lack of skilled labour, and work performance errors.